Improving hospital care for people who use drugs: deliberative process development of a clinical guideline for opioid withdrawal management - Marisha Wickremsinhe; Adam Holland; Jenny Scott; Rosalind Gittins; Michael Brown; Adrian 'Bean' Noctor; Dan Lewer; Vivian Hope; Niamh Eastwood; Magdalena Harris (BMC, 2024)
Abstract Background Management of opioid withdrawal in hospital settings is crucial to improve treatment completion and health outcomes among patients who use opioids, such as heroin. Evidence-based clinical guidelines can support responsive provision of opioid substitution therapy (OST). In England there is no standardised application of guidance for substance dependence management across National Health Service (NHS) Hospitals. A recent review of NHS hospital policies identified varying approaches to managing opioid withdrawal and procedural barriers to timely medication. Objective To develop a clinical guideline for opioid withdrawal management in acute NHS hospital trusts to be tested and evaluated as part of the iHOST (Improving Hospital Opioid Substitution Therapy) research intervention. Methods We undertook a deliberative guideline development process. The University London College Hospital (UCLH) substance dependence guideline was used as a template, with key points of revision informed by evidence review, consultations with hospital staff and people with opioid dependence. A multidisciplinary working group deliberated evidence statements to develop recommendations. These were reviewed by an oversight committee comprising representatives from key stakeholder organisations. The team authored the guideline with iterative review by the oversight committee, key stakeholders and UCLH clinical governance committees. Results Deliberation focused on three key domains: (1) identifying opioid dependence and promptly continuing existing OST prescriptions; (2) initiating or re-titrating OST; (3) ensuring safety and continuity of care at discharge. Changes to the UCLH guideline included removal of mandatory urine drug testing prior to OST; increasing initial methadone titration dose; and provision for a higher day-one titration dose when specific safety criteria are met. A new titration schedule for sublingual buprenorphine was incorporated. Discharge planning to ensure continuity of community care and reduce risk of opioid overdose was emphasised, with allowance for bridging prescriptions of OST and naloxone provision on hospital discharge. Conclusion The iHOST clinical guideline aims to remove procedural barriers to opioid withdrawal management for hospital inpatients. It is intended to be implemented by other NHS hospitals, which could improve access to OST and reduce discrepancies in treatment access and completion. Study registration ISRCTN47320412 https://doi.org/10.1186/ISRCTN47320412 .